Main factors influencing the digital economy: a literature review - Zhang, Heng (Management and Entrepreneurship: Trends of Development, 2024)
In response to the challenges of our time, our research aims to understand and analyse the trends of digitalization of the economy in the current context. It is important to note that this topic is becoming increasingly relevant in the context of the rapid development of technology and its impact on the global economy as a whole. To achieve the goals and objectives of the current study, a wide range of scientific sources were used, namely articles in periodicals, theses, books, etc. The global objectives of this research discourse are to study the impact of digitalization on the modernization of the international economy at both the micro and macroeconomic levels. Thus, one of the essential aspects of this movement is to understand and analyse the technological innovations that transform traditional industries and business models. The increasing role of digital technologies in the modern economy and their impact on the competitiveness of enterprises and countries in the global economic space is a pressing issue. Both technical and socio-economic consequences of digital transformation should be addressed when analysing this issue. The impact of digitalization on the employment structure and labour market is also important. Changes in the technological landscape can affect both the distribution of jobs and the development of skills required for a successful career, as well as lead to the emergence of new forms of labour. JEL Classification: L86